ANALYSIS OF INTENTIONAL APPLICATION OF STRUCTURAL PROGRAMS FOR LIFE SKILLS THROUGH PHYSICAL EDUCATION AND SPORTS ACTIVITIES IN THE FRAMEWORK OF POSITIVE YOUTH DEVELOPMENT - Yulianto, Ari Gana; Hendrayana, Yudy (Universitas Pendidikan Indonesia, 2022)
From some of the research found in articles on positive youth advancement, organized training and sports can produce quality programs to support positive youth improvement. This study aims to describe the results of research on an intentionally structured program to improve life skills through physical education and sports learning to develop positive youth. To cultivate positive youth. The information was obtained by examining 30 journal articles for consideration from 120 journal articles taken from 4 databases, namely Taylor and Francis, Google Scholar, Science Direct, and Sage, and with life skills, intentionally structured, positive youth development, physical education, and sports. The results of this study indicate that structured physical education and sports programs can produce quality programs. Where this can be concluded in line with widespread societal beliefs, mainly that structured programs are applied in physical education and sports in the community, their implementation can decisively affect youth's progress.